Narrative Accounting Practices in Indonesia Companies - Meutia, Inten; Putra, Budiawan Cimarko (Binus Business Review, 2017)
This research aimed to reveal creative accounting practices in the form of narrative accounting occuring in companies in Indonesia. Using content analysis, this research analyzed the management discussion and analysissection in the annual report on the group of companies whose performance had increased and declined in several companies listed on the Indonesian Stock Exchange. This research finds that the narrative accounting practices are applied in these companies. The four methods of accounting narratives are found in both groups of companies. There are stressing the positive and downplaying the negative, baffling the readers, differential reporting, andattribution.